2011
DOI: 10.1016/j.chemosphere.2011.02.071
|View full text |Cite
|
Sign up to set email alerts
|

Levels of persistent organic pollutant and their predictors among young adults

Abstract: Exposure to persistent organic pollutants (POPs), such as polychlorinated biphenyls (PCBs), dichlorodiphenyldichloroethane (p,p’-DDE), and hexachlorobenzene (HCB) continues to be of concern due to their ubiquitous distribution and high persistence. Current toxicant body burden is still a primary concern within the Akwesasne Mohawk Nation since other studies conducted within the community have shown relationships between these POPs and endocrine disruption. In this article we describe the levels of these toxica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
55
3
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 46 publications
(66 citation statements)
references
References 48 publications
7
55
3
1
Order By: Relevance
“…In agreement with Agudo et al (2009), the most consistent dietary predictors in our population were those for PCBs. In this regard, fatty food items were in general associated with POP levels, such as blue fish consumption, which showed a positive relationship with levels of PCB-138, PCB-153, PCB-180 and p,p′-DDE, confirming previous reports Bjermo et al, 2013;Gallo et al, 2011;Llop et al, 2010;Rivas et al, 2007). Llobet et al (2003) reported that PCB-153 was the most abundant persistent organic pollutant in food items, especially in fish.…”
Section: Predictors Of Serum Pop Concentrationssupporting
confidence: 85%
See 1 more Smart Citation
“…In agreement with Agudo et al (2009), the most consistent dietary predictors in our population were those for PCBs. In this regard, fatty food items were in general associated with POP levels, such as blue fish consumption, which showed a positive relationship with levels of PCB-138, PCB-153, PCB-180 and p,p′-DDE, confirming previous reports Bjermo et al, 2013;Gallo et al, 2011;Llop et al, 2010;Rivas et al, 2007). Llobet et al (2003) reported that PCB-153 was the most abundant persistent organic pollutant in food items, especially in fish.…”
Section: Predictors Of Serum Pop Concentrationssupporting
confidence: 85%
“…The finding that these variables have a stronger effect in comparison to the participants' history of breastfeeding/parity indicates an interesting cohort effect that affects the POP burden at an adult stage. In this regard, Gallo et al (2011) and Hsu et al (2014) also found positive associations between the receipt of breastfeeding and POP exposure. Both parity and lactation have been described as major routes for POP clearance (Cerrillo et al, 2006;Hansen et al, 2010;Hardell et al, 2010;Veyhe et al, 2015).…”
Section: Predictors Of Serum Pop Concentrationsmentioning
confidence: 61%
“…For both projects, all data collection was performed by project staff, all members of the Akwesasne community, and data were collected without prior knowledge of participants’ exposure status. Study protocols and methods have previously been described in detail (Gallo et al 2011; Newman et al 2006; Newman et al 2009; Schell et al 2003), and are briefly reviewed here.…”
Section: Methodsmentioning
confidence: 99%
“…Young adults were eligible if they had participated in MAWBs, and were now between 17 and 20 years of age (Gallo et al 2011). The YAWBs sample consisted of 154 participants; however two persons were omitted because reported organochlorine levels from our earlier study, MAWBs, were not available and one person was excluded because serum POP levels were not available from the follow-up study, leaving a final sample size of 151 individuals.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation